2011
DOI: 10.1007/s12646-011-0071-4
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering Culture and Self

Abstract: The interplay of culture and self has been one of the most active areas of research in self and identity. It has provided a number of theoretical concepts and research methodologies that have advanced the psychological understanding about self processes. This paper provides a concise review of the field's underlying assumptions, and points to its contemporary issues and future directions. In particular, we begin by reviewing the work of Triandis Psychological Review, 96, 506-520, (1989) and Markus and Kitaya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…For instance, independent self-construal is often found to be related to less social anxiety (e.g., Dinnel et al, 2002;Hong & Woody, 2007;Okazaki et al, 2002). However, the local socio-cultural context where these psychological processes become salient or even pathological is also important because both cultural contexts and the self are constantly undergoing negotiation and reformation within these local socio-cultural contexts (Kashima et al, 2011). As a result, it is crucial to consider cultural variations in social anxiety, OTKS, and psychopathology in general as a process in a given context, not a static mean difference between groups across all situations and locations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, independent self-construal is often found to be related to less social anxiety (e.g., Dinnel et al, 2002;Hong & Woody, 2007;Okazaki et al, 2002). However, the local socio-cultural context where these psychological processes become salient or even pathological is also important because both cultural contexts and the self are constantly undergoing negotiation and reformation within these local socio-cultural contexts (Kashima et al, 2011). As a result, it is crucial to consider cultural variations in social anxiety, OTKS, and psychopathology in general as a process in a given context, not a static mean difference between groups across all situations and locations.…”
Section: Discussionmentioning
confidence: 99%
“…Self-construals (i.e., independent vs. interdependent self-construals) alone do not fully account for cultural variations in SA and TKS (e.g., Dinnel et al, 2002). Indeed, studies of cultural variation in independent vs. interdependent self-construals have often yielded mixed results (Kashima, Koval, & Kashima, 2011;Norasakkunkit et al, 2012;Matsumoto, 2002).…”
Section: The Offensive-type Of Taijin Kyofushomentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few studies suggest that East Asian cultures differ from each other in subtle ways (e.g., Kashima et al, 1995;Yamaguchi et al, 2007), systematic explanations for such differences are yet lacking. Promisingly, Kashima, Koval, and Kashima's (2011) recent analysis of culture and self considers cultural change and history as a potential factor for explaining cultural differences between Japan and other Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Watkins, Yau, Dahlin, and Wondimu (1997) suggested that only the first 10 responses should be considered, and recommended use of the shorter (fewer items) and less abstract (better primed) versions of the TST. Kashima, Koval, and Kashima (2011) suggested dropping the pronoun "I" to minimize the impact of language structure and use in collectivist societies. Because our focus was on a group of bilingual ethnic Chinese in Hong Kong, we believed that asking respondents to complete 20 "Who am I?"…”
mentioning
confidence: 99%